Study on Telescopic Walkway Design of Jetty Gangway - P Dhinesh Kumar A/L Panneerchelvam, Dhinesh Kumar (Universiti Teknologi Petronas, 2009)
This project studies on the telescopic walkway design of the jetty gangway used in the oil and gas industry jetties. The objective of the project is to conduct study on the optimal design parameters for the telescopic walkway of gangway which suits the operational conditions at various jetties of the oil and gas companies in the South East Asia region. The limitations with respect to various marine terminal aspects are studied and the drawbacks are analyzed. Besides, the tidal conditions in the South East Asia region are surveyed to obtain the range of tidal conditions that the design must comply with. Upon gathering data regarding the standard structural beams which are appropriate for the design, static load analysis is done and the data is incorporated into a Microsoft Excel worksheet. This worksheet is a primary tool to analyze different parameters of the beams and its stress distributions. The study managed to produce results on the shear force, bending moments, shear stress and bending stress which would be essential to understand how telescopic beams are subjected to stress distributions. The study on the tidal conditions on the other hand has revealed the range of beam length that can be standardized for the South East Asia region.